A Cohort Study of Decompressive Craniectomy for Malignant Middle Cerebral Artery Infarction. Issue 25 (June 2015) - Hao, Zilong; Chang, Xueli; Zhou, Hongqing; Lin, Sen; Liu, Ming; Bix., Gregory
<x xml:space="preserve">Abstract</x> Abstract Decompressive hemicraniectomy with malignant middle cerebral artery (MCA) infarction is effective but remains underutilized. The aim of this study was to observe the utilization of this intervention in mainland China. We included patients with malignant MCA infarction who admitted in West China Hospital between December 2007 to March 2011. The outcomes were death and favorable outcome (mRS < 4) at 1 month and 1 year. The multivariate logistic regression model was used to identify the independent predictors for outcomes. Ten percent (219/2174) of patients with acute ischemic stroke had malignant MCA infarction and 31.1% (68/219) patients meet the criteria that ⩽60 years of age and the timing to hospital <48 hours after stroke onset. Of them, 18 patients (26.5%) underwent to decompressive hemicraniectomy. In total, 31 patients (14.2%) underwent the decompressive surgery. The average age was 53 ± 12 years; median NIHSS score was 21. The case fatality rate of patients in surgery group was significantly lower than those of in nonsurgery group at 1 month and 1 year follow-ups (32.3% and 38.7% vs. 51.1% and 61.2%, respectively, P < 0.05). Patients in surgery group had a higher proportion of good outcome at 1 year follow-up (32.2% vs. 13.3%, P = 0.006). After adjusting for confounders including age, sex, NIHSS score, and GCS score on admission, decompressive hemicraniectomy was an independent predictor of good outcome for 1 year (OR = 3.44, 95% CI, 1.27–9.31). This study shows better outcomes in the surgical group, which are consistent with findings in previous prospective randomized trials. However, this beneficial intervention remains underutilized in clinical settings.